A combined rheology and time domain NMR approach for determining water distributions in protein blends. (October 2016) - Dekkers, Birgit L.; de Kort, Daan W.; Grabowska, Katarzyna J.; Tian, Bei; Van As, Henk; van der Goot, Atze Jan
Abstract: We present a combined time domain NMR and rheology approach to quantify the water distribution in a phase separated protein blend. The approach forms the basis for a new tool to assess the microstructural properties of phase separated biopolymer blends, making it highly relevant for many food and non-food related applications. First, we determine the relaxation rate of absorbed water, and the viscoelastic properties of the separated phases as function of the water content. Next, the same properties are measured for the protein blends. Finally, predictions for water distribution obtained from rheological experiments are made via the polymer blending law, and compared to a more direct assessment of the water distribution with time-domain NMR relaxometry (TD-NMR). In this study, the protein blend consists of soy protein isolate (SPI) and vital wheat gluten (WG). We demonstrate that predictions for water distribution are similar for both TD-NMR and rheological measurements. It turns out that water does not distribute homogenously over the phases. Independent of the SPI and WG ratio, more water is absorbed by the SPI phase relative to the WG phase, which largely determines the resulting rheological properties of the blends. Graphical abstract: Highlights: TD-NMR is an adequate method for determining the water distribution in a SPI-WG blend. The viscoelastic properties of SPI-WG blends are determined by the water distribution between both phases. Water distributions derived from TD-NMR are in agreement with predictions made from rheological properties. Combination of TD-NMR and rheology can be used to describe the structure (formation) in dense biopolymer blends.